Biological degradation of aflatoxin M1 by Bacillus pumilus E‐1‐1‐1. Issue 3 (31st August 2018) - Gu, Xinxi; Sun, Jilu; Cui, Yuqi; Wang, Xianghong; Sang, Yaxin
Abstract: Aflatoxin M1 (AFM1 ) is a potent mycotoxin which causes serious health concerns in developing countries, where it is mainly found in milk, meat, and other foods. Biological detoxification is a promising method for eliminating AFM1 . The aim of this work was to search for AFM1 ‐degrading bacterial strains from animal waste, soil, and activated sludge. High‐performance liquid chromatography and Fourier‐transform infrared spectroscopy were used to analyze the AFM1 degradation products. A strain designated E‐1‐1‐1 was obtained from African elephants feces, with the degradation ratio of AFM1 reaching 89.55% in 12 hr. Based on morphology, physiological and biochemical tests, and 16S rRNA gene sequence analysis, strain E‐1‐1‐1 was identified as Bacillus pumilus . The culture supernatant of B. pumilus E‐1‐1‐1 degraded AFM1 effectively, whereas the cells and cell extracts of B. pumilus E‐1‐1‐1 were far less effective. Carbon and nitrogen sources had highly significant effects on the degradation of AFM1 by B. pumilus E‐1‐1‐1. The AFM1 ‐degrading strain, B. pumilus E1‐1‐1, could have great potential in industrial applications. Abstract : The biological detoxification is a promising method for eliminating AFM1. The goals this work was to search for AFM1‐degradation strains from the animal waste, soil and activated sludge. A strain named as E‐1‐1‐1 was obtained from African Elephants, which the degradation ratio of AFM1 could reach 89.55% in 72 hr.